Interaction between industrial textile dyes and cyclodextrins. (August 2015) - Semeraro, Paola; Rizzi, Vito; Fini, Paola; Matera, Sergio; Cosma, Pinalysa; Franco, Esther; García, Rocío; Ferrándiz, Marcela; Núñez, Estrella; Gabaldón, José Antonio; Fortea, Isabel; Pérez, Enrique; et al.
Abstract: The interactions between two industrial textile dyes in aqueous solution and a series of different commercial cyclodextrins (CDs) has been investigated at 25 °C by spectrophotometric and electrochemical measurements to study their efficiency in the removal of color from real textile wastewater. This is the first step of the objectives of LIFE + European project, DYES4EVER, which consists in the use of cyclodextrins for the treatment of textile industry wastewater (LIFE12 ENV/ES/000309). The main aim of DYES4EVER is the demonstration and validation of cyclodextrins as encapsulation agents for textile dyes from wastewater. This is in order to recover and reuse both clean water and dyes for other industrial processes. The molar extinction coefficients of dyes have been established by means of UV spectra, while Benesi–Hildebrand treatment has been proposed to evaluate the binding constants analyzing spectrophotometric and electrochemical data. Graphical abstract: Highlights: Two industrial dyeing formulations were studied in presence of CDs by spectroscopy. High binding constants were evaluated applying a modified Benesi–Hildebrand method. Electrochemistry let to hypothesized specific interaction sites between dye and CD.